Influence of chain length in protic ionic liquids on physicochemical and structural features of lignins from sugarcane bagasse - Pin, Thaynara C.; Brenelli, Lívia B.; Nascimento, Viviane M.; Costa, Aline C.; Pu, Yunqiao; Ragauskas, Arthur J.; Rabelo, Sarita C. [UNESP] (Elsevier, 2021)
The mechanisms behind lignin dissolution with protic ionic liquids (PILs) and their influence over lignin properties remain not fully explored. In this work, physicochemical and structural features of lignins extracted from sugarcane bagasse after pretreatment with a series of PILs (length of the cation chain combined with different anions) were assessed using analytical techniques. It was found that the lignin extracted with shorter chain length cations PILs showed the highest β-O-4 content. Opposite, the increase of the PILs cation chain length resulted in enhanced depolymerization. All lignins presented high polydispersity (>3.7), while the weight average molecular ranged from 1921 to 13,539 g/mol. The recovered [Eti][Mal] lignin presented the higher β-O-4 content and was possibly the most preserved lignin obtained. Opposite, lignin isolated from [Hex][Ac] and [Hex][For] treatments had less β-O-4 linkages attributed to the depolymerization of lignin via rupture of ether linkages generating intermediates that further repolymerized and/or depolymerized. These results suggest that the ionicity of the PIL is a crucial factor for lignin dissolution. Furthermore, these results illustrate that the proposed pretreatment using different PILs is useful to obtain high-quality lignins with distinct features and opens a new perspective for materials to match various applications.
Keywords: Biorefinery; Lignin; Physicochemical characterization